Assessment of the stability and plasticity of productivity indices and quality of new soft winter wheat varieties under the conditions of Forest Steppe of Ukraine - П. М. Василюк (Plant Varieties Studying and Protection, 2014)
The article highlights the research results of stability and plasticity of soft winter wheat varieties under the conditions of Forest Steppe of Ukraine. The article determines action of abiotic and biotic factors of a certain environment on genotype and bases the degree of their influence on the growth, development, yield and quality of soft winter wheat. The obtained result allows recommending varieties of soft winter wheat: Lira odeska, Tonatsiya, Arktis, Etela, for producers as the most suitable varieties for intensive cultivation technologies in Forest Steppe zone of Ukraine.